Assessment of small-intestine permeability in healthy Nigerian children is altered by urinary volume and voiding status. - Ibukun Afolami; Folake Olukemi Samuel; Martin Mwangi; Michael Oderinde; Marlies Diepeveen-de Bruin; Alida Melse-Boonstra (PLoS ONE, 2021)
Objective This study aimed to uncover the effect of voided urinary volume on small intestine permeability ratios in healthy children. Methods We assessed small intestine permeability in 155 apparently healthy children, aged 3-5 years old, without any visible symptoms of disease, in a rural, malaria-endemic setting in Nigeria, using a multi-sugar test solution, comprising lactulose, sucrose, mannitol, and rhamnose. Children were categorized into low urinary volume (LV) and high urinary volume (HV), based on the volume of urine voided per kg body weight per hour. LV children voided less than 25th percentile of the total population, while HV children voided greater than 75th percentile of the total population. Urinary volume excreted over a 90-minute period after administration of the test solution was measured, and differences in sugar ratios were compared between children with high (HV) and low urinary volumes (LV), as well as between children who voided (VC) or who were not able to void (NVC) before administration of the test solution. Results Urinary mannitol and rhamnose recovery were 44% (p = 0.002) and 77% (p<0.001) higher in HV children compared to LV children respectively, while urinary lactulose recovery was 34% lower (p = 0.071). There was no difference in urinary sucrose recovery between groups (p = 0.74). Lactulose-mannitol ratio, lactulose-rhamnose ratio and sucrose-rhamnose ratio were all significantly higher in children in the LV group compared to children in the HV group (p<0.001). In a multiple regression analysis, urinary volume and voiding status combined, explained 13%, 23% and 7% of the variation observed in lactulose-mannitol, lactulose-rhamnose and sucrose-rhamnose ratios, respectively. Conclusion Sugar permeability ratios vary significantly with total urinary volume in multi-sugar small-intestine permeability tests. Voiding status before sugar administration appears to influence lactulose recovery, lactulose-rhamnose and sucrose-rhamnose ratios independently of total urinary volume. Evidence from this study suggests the need to take urinary volume into account when conducting multi-sugar small-intestine permeability tests.